Pharmacologically targeting tribbles gene expression in colorectal cancer - Yassuda, Victor (2022)
TRIB1, TRIB2 and TRIB3 belong to the mammalian Tribbles family of pseudokinases proteins. Several studies reported Tribbles oncogenic role in different types of cancer, including colorectal cancer (CRC).